2012
DOI: 10.1161/atvbaha.112.00009
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Plasma High-Density Lipoproteins Inhibits Development of Experimental Abdominal Aortic Aneurysms

Abstract: Objective-Patients with abdominal aortic aneurysms have lower concentrations of high-density lipoproteins (HDLs), leading us to investigate whether increasing plasma HDLs could influence aneurysm formation. Methods and Results-Using the angiotensin II−induced hypercholesterolemic and the CaCl 2 -induced normocholesterolemic mouse model of AAA, we investigated the hypothesis that elevation of HDLs inhibits AAA. HDLs elevated before or at the time of AAA induction reduced AAA formation in both models but had no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 60 publications
2
24
1
Order By: Relevance
“…Recent evidence suggests that increasing plasma high density lipoprotein-c lowers the incidence of AngII-induced AAAs. 40,41 These observations are in accordance with reports that TGF-β1 blocking strategies promote plaques with a rupture-prone phenotype in ApoE −/− mice. 42,43 Atherosclerosis continued to progress in ApoE −/− mice after 2 weeks of AngII infusion, suggesting that a transient increase in AngII can have prolonged effect on atherosclerosis progression.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…Recent evidence suggests that increasing plasma high density lipoprotein-c lowers the incidence of AngII-induced AAAs. 40,41 These observations are in accordance with reports that TGF-β1 blocking strategies promote plaques with a rupture-prone phenotype in ApoE −/− mice. 42,43 Atherosclerosis continued to progress in ApoE −/− mice after 2 weeks of AngII infusion, suggesting that a transient increase in AngII can have prolonged effect on atherosclerosis progression.…”
Section: Downloaded Fromsupporting
confidence: 90%
“…Several evidences from the literature, including our data, highlight the role of MAPK in AAA development [20,21,28]. All three subclasses of MAPK have been shown to be activated in Angiotensin II-induced AAA formation.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 69%
“…We have previously documented that infusion of Angiotensin II-induced production of a number of proinflammatory proteins in the early stages of AAA development [20,21]. Having shown that These data demonstrate that IAXO-102 treatment is a negative regulator of Angiotensin II driven inflammation and TLR4 signalling is the target by which IAXO-102 exerts its effect.…”
Section: Iaxo-102 Downregulates Tlr4 Signalling In Mouse Aortamentioning
confidence: 73%
“…31 However, it is reported that phosphorylation of ERK and JNK vary by the region of aorta. 32 Because we used whole aortic tissues to examine protein expression, this apparent discrepancy may have occurred because of these concerns. Meanwhile, AngII is known to induce mitogen-activated protein kinase (MAPK) phosphorylation in THP-1 cells.…”
Section: Sawada Et Al Iron and Abdominal Aortic Aneurysm 1513mentioning
confidence: 99%